The effect of tennis match play on joint range of motion in junior players - Srimpf, R.; Filipcic, T.; Filipcic, A. (Acta Gymnica, 2019)
Background: Tennis players perform a large number of multidirectional and cutting movements, together with asymmetrical rotational motions resulting from serves and groundstrokes. Numerous shot repetitions and multidirectional motions directly influence a tennis player's upper and lower extremity joint range of motion (ROM).